Protocol for a gender-sensitised weight loss and healthy living programme for overweight and obese men delivered in Australian football league settings (Aussie-FIT): A feasibility and pilot randomised controlled trial. Issue 10 (17th October 2018) - Quested, Eleanor; Kwasnicka, Dominika; Thøgersen-Ntoumani, Cecilie; Gucciardi, Daniel F; Kerr, Deborah A; Hunt, Kate; Robinson, Suzanne; Morgan, Philip J; Newton, Robert U; Gray, Cindy; Wyke, Sally; McVeigh, Joanne; et al.
Abstract : Introduction: Overweight and obesity are highly prevalent among Australian men. Professional sports settings can act as a powerful 'hook' to engage men in weight loss programmes; the Football Fans in Training programme delivered in professional UK soccer clubs was successful and cost-effective in helping men lose weight. The Australian Football League (AFL) is a potentially attractive setting to engage men in a weight loss programme. We aim to develop, pilot and evaluate the feasibility of a weight loss intervention for overweight/obese middle-aged men, delivered in AFL settings, to promote weight loss and healthier lifestyles and determine its suitability for a future randomised control trial. Methods and analysis: 120 overweight/obese male fans will complete baseline physical and psychological health measures and objective measures of physical activity (PA), weight, waist size and blood pressure prior to randomisation into the intervention or waitlist comparison group. The intervention group will receive 12 weekly 90 min workshops incorporating PA, nutrition education, behaviour change techniques and principles of effective motivation. Four community coaches will be trained to deliver Aussie-FIT at two AFL clubs in Western Australia. Measurements will be repeated in both groups at 3 months (post-intervention) and 6 months (follow-up). Outcomes will include programme uptake, attendance, changes in lifestyle and weight variables to inform power calculations for a future definitive trial, fidelity of programme delivery, acceptability, satisfaction with the programme and perceptions of effectiveness. We will also determine trial feasibility and potential to gather cost-effectiveness data. Ethics and dissemination: Ethics approval was granted by Curtin University's Human Research Ethics Committee (HREC2017-0458). Results will be disseminated via peer-reviewed publications, conference presentations and reports. A multicomponent dissemination strategy will include targeted translation and stakeholder engagement events to establish strategies for sustainability and policy change. Trial registration number: ACTRN12617000515392; Pre-results.